Knowledge, understanding and perceptions of key stakeholders on the maternity protection available and accessible to female domestic workers in South Africa. - Catherine Pereira-Kotze; Mieke Faber; Tanya Doherty (Public Library of Science (PLoS), 2023)
Maternity protection enables women to combine reproductive and productive roles. Domestic workers are a vulnerable group due to heterogeneous non-standard employment relationships and are unlikely to have access to comprehensive maternity protection. This study aimed to explore the knowledge, understanding and perceptions of key stakeholders in government, trade unions, non-governmental organisations and other relevant organisations of the maternity protection entitlements that should be available and accessible to female domestic workers in South Africa. This qualitative cross-sectional study included in-depth interviews with fifteen stakeholders working in different sectors in South Africa and mainly at a national level involved in maternity protection availability and access. Results show that stakeholders appear to have limited understanding of comprehensive maternity protection. Many challenges related to accessing cash payments while on maternity leave were described and suggestions were provided for how this could be improved. Participants described how certain labour-related characteristics unique to the domestic work sector were barriers in accessing maternity protection. Ensuring greater awareness of all components of maternity protection and improving implementation of existing labour legislation intended to guarantee maternity protection for non-standard workers in South Africa is important to improve access to maternity protection for this vulnerable group. Improved access to maternity protection would contribute to optimal maternal and new-born health and ensure economic security for women around the time of childbirth.